ROLE OF SELECTIVE ESTROGEN RECEPTOR MODULATORS (SERM) IN TREATMENT OF CARCINOMA PROSTATE. - PRATAP SHANKAR,; D.K. KATIYAR,; RAKESH KUMAR DIXIT, (International Journal of Pharma and Bio Sciences, 2013)
The exact mechanism of carcinogenesis is unknown, although it is believed to involve a combination of dietary, environmental, genetic, lifestyle and hormonal causes. Prostate cancer is main problem of men, and it is believed that prostate cancer is the hormonal imbalance of the testosterone but now it has been proved clinically that estrogen hormone imbalance is also involved in the prostate carcinogenesis during the development or later period of the prostate. It required maintaining the balance of the estrogen hormone by some estrogen receptor. In this review we focused on the literature survey on Selective estrogen receptor modulators (SERMs) in prostate carcinogenesis and prevention because SERMs have shown the ability to prevent and treat prostate cancer.